PENGARUH PERSEPSI PENGHARGAAN FINANSIAL, NILAI-NILAI SOSIAL, PERTIMBANGAN PASAR KERJA, DAN PENGETAHUAN AKUNTANSI TERHADAP PEMILIHAN PROFESI AKUNTAN PUBLIK PADA MAHASISWA AKUNTANSI FAKULTAS EKONOMI UNIVERSITAS SARJANAWIYATA TAMANSISWA YOGYAKARTA - Afdatil, Afdatil; Erawati, Teguh; Wardani, Dewi Kusuma (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2021)
This study aims to examine whether perceptions of financial rewards, social values, labor market considerations, and accounting knowledge on the choice of public accountants for accounting students at the Faculty of Economics, University of Sarjanawiyata Tamansiswa Yogyakarta. This research method uses quantitative and primary descriptive methods by using a questionnaire. The study took a sample of 80 accounting students of the Faculty of Economics, University of Sarjanawiyata Tamansiswa Yogyakarta. The sampling technique used snowball sampling. Data collection was carried out using a questionnaire in the form of a google form questionnaire to be distributed to other respondents with the aim of obtaining data from respondents. The number of questionnaires processed was 80 questionnaires. Data were analyzed using multiple linear regression analysis. The results of this study indicate that financial rewards have a ngative effect on the choice of the public accounting profession. Social values, do not affect the choice of the public accounting profession. Meanwhile, labor market considerations affect the choice of the public accounting profession and accounting knowledge does not affect the choice of the public accounting profession.Keywords: Perceptions of Financial Rewards, Social Values, Labor Market Considerations, Knowledge of Accounting, and Selection of the Professional Public Accountant